AJPLung v1 - Manuel Richter (2021)
Invasive ventilation with oxygen supplementation may inadvertently cause ventilator- and hyperoxia-induced lung injury, respectively, but their balance is fairly unaddressed. The concept of mechanical power summarizes factors of ventilation intensity associated with development of ventilator-induced lung injury. More recently, we introduced the theoretical framework for chemical power to estimate risk of hyperoxia-induced injury and allow for integration of both mechanical and chemical energy transfer per unit time. In the current study, we explored the associations of mechanical and chemical power with outcomes in mechanically ventilated patients with acute respiratory distress syndrome. In this secondary analysis of six pooled cohort studies, patients with acute respiratory distress syndrome per Berlin criteria and available data to calculate chemical and mechanical power on days 1 and 2 of invasive ventilation were selected. The primary outcome was all-cause 60-day mortality. A total of 2,117 patients were included in the main analysis. Higher chemical power levels were associated with increased 60-day mortality (P < 0.001), regardless of the mechanical power levels. Increasing mechanical power levels combined with decreasing chemical power levels was associated with a better outcome than vice versa (P < 0.001). There was no interaction between both powers. In this pooled cohort study of acute respiratory distress syndrome patients receiving invasive ventilation, higher chemical power levels were associated with a higher rate of mortality, independent of mechanical power levels. These results support further experimental validation of the concept of chemical power and exploration of its balance with mechanical power to predict outcome of lung injury.